Social Reactions and Reasoned Pathways of High School Students and School Dropouts' Inclination toward Smoking Behavior: Prototype/willingness Modelling via Generalized Structural Equation - Mohammad ASGHARI JAFARABADI; Haidar NADRIAN; Hamid ALLAHVERDIPOUR (Tehran University of Medical Sciences, 2018)
Background: To investigate the determinants of smoking behavior among Iranian adolescents applying the Prototype/Willingness (P/W) Model. Methods: In this cross-sectional study, a self-administered P/W model-based questionnaire was completed between 760 randomly selected adolescents (high school students and dropouts) in Hamadan, Iran, in 2015. Generalized structural equation modeling (GSEM) was applied to analyze data. Results: Significant associations were found between subjective norms and positive attitudes toward smoking (P<0.001). The behavioral intention was also significantly related to the willingness and subjective norms (P<0.001). Prototype or risk image was not significantly related to the willingness among the dropout adolescents. Conclusion: When social reaction and reasoned processes are modeled together, both may predict the smoking behavior. The high-risk perception and the high-risk image toward smoking behavior among the adolescents may originate from socio-cultural factors underlying the behavior. Further research is recommended to investigate the socio-cultural biases of the issue.